Recipes: Communicative Function of Sentences - Procházková, Ilona (Univerzita Pardubice, 2011)
This thesis focuses on the communicative function of sentences in cookery recipes. Firstly the stylistic part defines main components of the recipe - introduction, name, ingredient list, directions, yield, notes, and nutrition information. Then this part describes the stylistic features of this type of discourse where the main focus is placed on briefness and clarity. In the theoretical part description of sentence in general is provided. Further, four speech-act functions are outlined and their correspondence with structural types or forms is expressed. Consequently command, statement, question, and exclamation clauses are examined in greater detail. Further it is disclosed that the last two do not appear in the discourse at all. Last section of the theoretical part is formed by discussion about politeness. It is emphasized that although the cookery recipes consist mainly of imperatives that are usually impolite and may generally cause fear, the discourse of cookery recipe is not offensive. The last part comprises of the quantitative analysis. The data is elaborated according to individual forms and functions, and number of occurrence is tabulated. It is shown that only commands and statements occur. The presupposition of imperatives as the most prevalent presented throughout the thesis is finally vindicated. Moreover, summary concerning non-finite structures, sentences types and recipe structure of both appendices is added.
Komunikativní funkce vět v kuchařských receptech
Keywords: komunikativní funkce vět; věty; imperativy; zdvořilost; kuchařské recepty; communicative function; sentences; imperatives; politeness; cookery recipes